2011
DOI: 10.1080/07448481.2010.540764
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and Reproductive Health Behaviors of California Community College Students

Abstract: The data provide justification for broader educational programs and access to family planning services, condoms, and HIV testing on community college campuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
45
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 16 publications
4
45
2
Order By: Relevance
“…Among heterosexual college students and gay men, two groups at high risk of STIs (Trieu, Bratton, & Marshek, 2011;CDC, 2013), there is strong evidence that the monogamy message has been heard. Rates of monogamous-identified relationships have significantly increased over time for both populations (Gotta et al, 2011).…”
Section: Monogamymentioning
confidence: 99%
“…Among heterosexual college students and gay men, two groups at high risk of STIs (Trieu, Bratton, & Marshek, 2011;CDC, 2013), there is strong evidence that the monogamy message has been heard. Rates of monogamous-identified relationships have significantly increased over time for both populations (Gotta et al, 2011).…”
Section: Monogamymentioning
confidence: 99%
“…3 Importantly, this recommendation applies to both men and women as research has shown that gender differences exist in the receipt of SRH care, with men using health care services substantially less than women. 4, 5 Further, studies suggest men and women face different barriers to discussing or receiving SRH services with health care providers. 6, 7 …”
mentioning
confidence: 99%
“…Although 4-year college students tend to report higher binge drinking (Paschall, Bersamin, & Flewelling, 2005) problem, alcohol use is known to be prevalent among community college students as well (Arliss, 2006; Sheffield, Drakes, Del Boca,& Goldman, 2005; Vankim et al, 2010). Research has highlighted the need and importance of studying dietary behavior (Arliss, 2007; Nelson, Larson, Barr-Anderson, & Neumark-Sztainer, 2009; Shive & Morris, 2006), physical activity (Sullivan et al, 2008; Vankim et al, 2010), and sexual behavior (Rich, Holmes, & Hodges, 1996; Trieu, Bratton, & Marshak, 2011) among community college students. Despite the needs, however, community college students remain understudied and underserved with regard to health behavior research and health promotion interventions, respectively (Chiauzzi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%